Examining the Influence of Ownership Structures on Firm Value Through Shariah-Compliant Profitability: An Empirical Study on Islamic Firms - Indah Wahyuni Sitohang (Jurnal Ilmiah Mahasiswa Raushan Fikr, 2024)
This study investigates the impact of various ownership structures—managerial, institutional, foreign, and domestic—on the value of Sharia-based companies, with profitability as a mediating variable. Employing a quantitative approach grounded in positivism, the research examines companies listed on the Sharia Stock Exchange from 2019 to 2022. A systematic methodology is used, involving variable identification, data collection, and statistical analysis using Econometric Views (Eviews) 9 through a multiple regression model. The sample comprises 30 companies from the JII index, selected via purposive sampling, and uses balanced panel data. The results indicate that managerial (p = 0.5551), institutional (p = 0.0922), foreign (p = 0.8073), and domestic ownership (p = 0.0651) do not significantly influence firm value when mediated by profitability. Consequently, the hypotheses are rejected, demonstrating that ownership structures alone do not enhance firm value through profitability in Sharia-based companies. These findings contribute to the understanding of ownership-performance dynamics and highlight the necessity to consider additional factors affecting firm value